A new species of decorator crabs, genus Menaethiops Alcock, 1895 (Crustacea: Decapoda: Brachyura: Majoidea: Epialthidae), from Abu-Musa Island, Persian Gulf, Iran - Naderloo, Reza (Zootaxa, 2015)
Menaethiops abumusa n. sp. is closely similar to M. bicornis Alcock, 1985, and M. gadaniensis Kazmi & Tirmizi, 1999, regarding the relatively contiguous rostral spines. The new species is easily distinguishable from its two congeners by having distinctly round angles of orbital eaves and distally divergent rostral spines. Whereas in M. bicornis, and M. gadaniensis, the angles of orbital eaves are anteriorly produced and rostral spines are closely attached to each other along their entire length.  Other morphological differences include the carapace spination/granulation, basal antennal segments, and morphology of the male’s first gonopod. Menaethiops gadaniensis was described from Gadani, Pakistan and was only known from the type locality, but is here recorded for the first time from the Gulf of Oman.